The limit Riemann solutions to nonisentropic Chaplygin Euler equations - Lin Maozhou; Guo Lihui (Open Mathematics, 2020)
We mainly consider the limit behaviors of the Riemann solutions to Chaplygin Euler equations for nonisentropic fluids. The formation of delta shock wave and the appearance of vacuum state are found as parameter εε tends to a certain value. Different from the isentropic fluids, the weight of delta shock wave is determined by variance density ρρ and internal energy H. Meanwhile, involving the entropy inequality, the uniqueness of delta shock wave is obtained.